Integrasi Transformasi Digital melalui Pendekatan Balanced Scorecard pada PT. Bank NTT - Malut, Maria Goreti; Baso, Susana Purnamasari; Timuneno, Antonius Yohanes William (Jurnal Akuntansi, Keuangan, dan Manajemen, 2025)
Purpose: This research seeks to examine the impact of the Balanced Scorecard (BSC) on the successful implementation of digital transformation within the company. Methodology/approach: This research utilized a descriptive approach combined with a mixed-method strategy. The data collected included both qualitative and quantitative information. Additionally, researchers conducted field surveys to obtain data through interviews and questionnaire responses. Results/findings: PT. Bank NTT, Tbk has maintained sustainable performance through the implementation of the Balanced Scorecard (BSC), which supports digital transformation, balances strategic goals with technology, and drives long-term business growth. Conclusions: The integration of the Balanced Scorecard, digital technology, and the SDGs perspective has proven effective in improving organizational performance. This approach supports better decision-making and contributes to sustainable development. Limitations: The study focuses on BSC-based digital transformation at PT. Bank NTT, Tbk, highlighting service digitization, business transformation, and employee performance. Future research should strengthen the fintech ecosystem and update BSC indicators. Contribution: As a consideration for PT. Bank NTT, Tbk in analyzing performance by increasing the digital transformation of services to customers and the community. This study can also serve as a literature review for further research on how well businesses do when using the BSC method.